The marked dextro-dominance causes accentuated morphophysiological variations in the female reproductive organs of the bat Molossus molossus - Ferraz, Juliana F.; de Oliveira, Rodrigo S.; Santiago, Cornélio S.; Soares, Emília M.; Morielle-Versute, Eliana [UNESP]; Taboga, Sebastião R. [UNESP]; Beguelini, Mateus R. (Elsevier, 2023)
Molossus molossus is an insectivorous molossid bat that is important in the control of nocturnal insects. It is the nominal and the most representative species of the family. However, there are few studies about its reproduction. Thus, this study aimed to evaluate variations of its female reproductive organs during the different reproductive phases. Twenty adult females, divided into four sample groups (non-reproductive, early and advanced pregnancy and lactation), were submitted to morphological and morphometric analyses. Results show that the female reproductive system of M. molossus is composed of ovaries, a short bicornuate uterus, slightly convoluted uterine tubes and vagina. The system presents a distinct morphofunctional asymmetry, with a marked dextro-dominance. The right ovaries of all analyzed groups (NON, P1, P2, and LAC) showed follicles at different stages of development, a large number of interstitial glands and a small, but persistent corpus luteum. Ovulation is simple, unilateral and preferential, occurring exclusively in the right ovary. Follicular development in the left ovary usually does not pass the secondary stage. Implantation is fundic and preferential, occurring exclusively in the right uterine horn. The placenta is formed with two distinct chorioallantoic portions, one diffuse endotheliochorial, which covers the entire uterine cavity and regresses in the final stages of pregnancy, and the principal discoidal hemochorial portion, formed in the implantation site. The uterine cervix presents a pseudostratified epithelium, while the vagina has a little keratinized stratified epithelium, which does not accentually vary in the different reproductive stages, but can disrupt and shed in some cases.
Keywords: Chiroptera; Giant cell; Ovary; Uterus; Vagina